1999
DOI: 10.1038/sj.onc.1202488
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E dependent kinase activity in human breast cancer in relation to cyclin E, p27 and p21 expression and retinoblastoma protein phosphorylation

Abstract: The cell cycle machinery is regulated by cyclin dependent kinases and sets of activating and inhibitory proteins. The G1-S control mechanism is often deregulated in tumours supposedly leading to increased kinase activity, phosphorylation of substrates and subsequent S phase entrance. Increased kinase activity has been proposed to be essential in cell cycle aberrations, but few studies have actually shown enhanced kinase activity related to speci®c cell cycle defects in primary tumours. In the present study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 42 publications
(48 reference statements)
1
33
0
Order By: Relevance
“…A number of studies have demonstrated a strong correlation between elevated levels of cyclin E1 and tumor progression and mortality (Muller-Tidow et al, 2001;Geng et al, 2001;Keyomarsi et al, 1994; GrayBablin et al, 1996;Loden et al, 1999;Nielson et al, 1996;Porter et al, 1997;Bortner and Rosenberg, 1997). In addition, there is a correlation between elevated cyclin E1-Cdk2 kinase activity, increased phosphorylation of Rb, and increased rates of tumor cell proliferation in breast cancers (Loden et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated a strong correlation between elevated levels of cyclin E1 and tumor progression and mortality (Muller-Tidow et al, 2001;Geng et al, 2001;Keyomarsi et al, 1994; GrayBablin et al, 1996;Loden et al, 1999;Nielson et al, 1996;Porter et al, 1997;Bortner and Rosenberg, 1997). In addition, there is a correlation between elevated cyclin E1-Cdk2 kinase activity, increased phosphorylation of Rb, and increased rates of tumor cell proliferation in breast cancers (Loden et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is a correlation between elevated cyclin E1-Cdk2 kinase activity, increased phosphorylation of Rb, and increased rates of tumor cell proliferation in breast cancers (Loden et al, 1999). However, the expression and activity of cyclin E2 in solid tumors is largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer cells, Cdk2 activity does not necessarily correlate with cyclin E levels (35) and may instead reflect the relative amounts of cyclin E and p27Kip1 (36). Cdk2 activity is turned on in quiescent MCF-7 cells by E2 without significant changes in cyclin E expression and instead relates to changes in association of cyclin E-Cdk2 with CIP͞KIP Cdk inhibitors (37).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of cyclin E-CDK2 activity in these tumors correlate with a high cyclin E/low p27 Kip1 phenotype (13) …”
Section: ) Functional Expression Of P27mentioning
confidence: 92%